CTLA-4 +49 A/G Polymorphism and the Risk of Lung Cancer: a Meta-analysis - Zhengliang WEI; Shaoqin ZHANG; Jian HU (Chinese Journal of Lung Cancer, 2021)
Background and objective: Lung cancer is one of the malignant tumors. Gene mutations associated with cellular immune function and regulating the activation and proliferation of immune cells. Several publications have explored the relationship between cytotoxic T lymphocyte antigen-4 (CTLA-4) +49 adenine (A)/guanine (G) polymorphism and susceptibility of lung cancer, but the results remain controversial. Thus, we performed this meta-analysis to derive a more comprehensive estimation of the relationship.  Methods: All articles addressed lung cancer and polymorphisms of CTLA-4 were searched from the PubMed, EMBASE databases published up to June 29, 2019. Odds ratios (ORs) with 95% confidence intervals (CIs) were used to assess the strength of association. Publication bias of relevant studies was examined via Begg’s test and funnel plots.  Results: The meta-analysis included 8 case-control studies covering 4,430 lung cancer patients and 5,198 healthy controls from September 2008 to April 2020. The overall eligible data indicated that CTLA-4 +49A/G polymorphisms did not correlate with the elevated lung cancer risk in all genetic comparison models (dominant model: OR=1.037, 95%CI: 0.925-1.161; recessive model: OR=0.968, 95%CI: 0.888-1.055; allele model: OR=0.992, 95%CI: 0.933-1.054; homozygous model: OR=0.980, 95%CI: 0.857-1.121; heterozygous model: OR=1.023, 95%CI: 0.906-1.154). In further stratified analyses, CTLA-4 +49A/G polymorphism was found to be significantly associated with susceptibility to NSCLC in these models (dominant model: OR=1.404, 95%CI: 1.074-1.836; allele model: OR=1.273, 95%CI: 1.034-1.565; homozygous model: OR=1.553, 95%CI: 1.044-2.310; heterozygous model: OR=1.308, 95%CI: 1.062-1.611).  Conclusion: CTLA-4 +49A/G polymorphism were not associated with the risk of lung cancer but might be a risk factor only in NSCLC.